Effectiveness of prophylaxis for hepatitis B in infants born to mothers serologically positive in Benghazi Medical center - Kadwar, Aziza; Mustafa, Marium; Shreef, khadiga; Ziuo, Fatma (Libyan Journal of Science &Technology, 2022)
Background: The seroprevalence of HBs Ag among the general population in Libya was found to be 2.2 %. Libya is therefore considered an area of intermediate endemicity for hepatitis B. vertical transmission is considered as the main route of spread of this infection. Trans placental (intra-uterine) transmission is presumed to cause the minority. Risk factors for transmission of HBV include maternal HBe Ag positivity, HBs Ag titer, and HBV viral load. Active immunization with hepatitis B vaccine (Hep. B vaccine), and hepatitis B immunoglobulin (HBIG) is 85-95% effective in preventing the disease. The objective of the study: To assess the effectiveness of hepatitis B vaccine and hepatitis B immunoglobulin in the prevention of the Hep. B. virus transmission and to study the factors that affected the immune response of the newborn babies of mothers with hepatitis B positive infection during pregnancy. Patients & Methods: A longitudinal cross-section study included 40 babies born to mothers with hepatitis B during the period from 1.1.2017 To 1.3.2019 at Benghazi Medical Center. The newborn babies have been immunized with Hepatitis BIG and Hepatitis B vaccine at birth, and further 3 doses of hep. B vaccine and HBIG. Multivariable analyses were done to assess the statistical significance associated with responders and nonresponders to HB immune prophylaxis. Results: all babies were negative for hepatitis Bs Ag in 40(100%), 35 (88%) their viral load was 10 mlIU/ml) in More than two-thirds (60%) and (63%) of infants at 9 months and 12 months respectively. Birth weight >2.5 kg was significantly associated with immune response >10 mIU/ml, whereas, Maternal viral load, time of administration of HBIG, and hep. B vaccine, gestational age, mode of delivery, type of feeding were statistically not significant. Conclusion: the study reported that all the newborn babies were negative for hepatitis B sAg after delivery, more than two-thirds of the babies were responders to immune-prophylaxis, and birth weight of >2.5kg was significantly related to high immune-response.